CHLOROPHYLL A__- CONCENTRATIONS MEASURED IN THE SOUTHERN OCEAN DURING THE 1984/85 CRUISE OF THE SHIRASE TO AND FROM SYOWA STATION, ANTARCTICA - フクダ, ヤスシ; オオノ, マサオ; ハツトリ, ヒロシ; フクチ, ミツオ; FUKUDA, Yasushi; OHNO, Masao; HATTORI, Hiroshi; FUKUCHI, Mitsuo (National Institute of Polar Research, 1986)
P(論文) departmental bulletin paper